The effect of electrons surface scattering on fine metal particle electromagnetic radiation absorption - Kuznetsova, I.A.; Lebedev, M.E.; Yushkanov, A.A. (Condensed Matter Physics, 2014)
The magnetic dipole absorption cross section of spherical shaped metal particle was calculated in terms of kinetic approach. The particle considered was placed in the field of plane electromagnetic wave. The model of boundary conditions taking into account the dependence of the reflectivity coefficient both on the surface roughness parameter and on the electrons incidence angle was investigated. The results obtained were compared with theoretical computation results for model of combined diffusion-specular boundary conditions of Fuchs. Перерiз магнiтної дипольної адсорбцiї металiчної частинки сферичної форми розраховано в термiнах кiнетичного пiдходу. Частинка, що розглядається, була помiщена в поле плоскої електромагнiтної хвилi. Дослiджувалась модель граничних умов, що враховує залежнiсть коефiцiєнта вiдбивання як вiд параметра
жорсткостi поверхнi, так i вiд кута налiтання електрона. Отриманi результати порiвняно з результатами
теоретичних розрахункiв для моделi комбiнованих дифузiйно-дзеркальних граничних умов Фучса.